“Aku Kap Kam, Kam Kap Aku” Kesadaran Kontingensi Richard Rorty dan Relevansinya dalam Budaya Solidaritas “Aron” - Eikel Ginting (Studia Philosophica et Theologica, 2023)
Living together as a whole of creation fosters the value of togetherness, which is manifested in thoughts and actions in relation to others. However, the challenge in realizing shared relations arises along with the development of the times, especially the increasing understanding of individualism and hedonism. This has an impact on ignoring human values, and does not provide opportunities for others to be respected and get the same life opportunities from a human standpoint. This is where awareness as an individual is needed as an awareness of contingency, to form pragmatism for the realization of opportunities in the human space. This is also relevant to the values of "aron", in the essence of life for the Karo people. Through this writing, the identity of limitations as a human becomes a contextual identity in strengthening the value of solidarity.